Impak pengalaman mengajar terhadap integrasi teknologi dalam pengajaran sirah dan tamadun islam - Jahidih Saili; Muhamad Suhaimi Taat; Nurul Hamimi Awang Japilan (Universiti Sultan Zainal Abidin, 2025)
The digital revolution has drastically transformed the educational landscape, making technology integration a necessity in contemporary education systems, including Islamic Education. However, its implementation in teaching Islamic History and Civilization has yet to reach optimal levels. This study aims to analyze the level of technology integration based on teachers' teaching experience, investigate the relationship between teaching experience and technological knowledge, and examine the interaction effect of teaching experience and Technological Pedagogical Content Knowledge (TPACK) on technology integration. A quantitative approach with a cross-sectional survey design was employed, involving 300 Islamic Education teachers in Sabah. Data were analyzed using one-way ANOVA and hierarchical multiple regression. Results revealed significant differences in technology integration levels among teaching experience groups, with novice teachers demonstrating higher integration levels compared to experienced teachers. A significant effect of interaction between teaching experience and TPACK on technology integration was also identified. These findings highlight the need to redesign teacher professional development programs and teacher training curricula. A more comprehensive approach tailored to teachers' experience levels is required to enhance the effectiveness of technology integration in teaching Islamic History and Civilization.